Exploring The Sustained Effects Of Brand Trust On Revisit Intention: An Empirical Study - Syah, Tantri Yanuar Rahmat; Setyawan, Dody; Rojuaniah, Rojuaniah; Astuti, Puji; Suyitno, Edy (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Brand trust is very important because it can contribute to loyalty in service use and consistent loyalty. The purpose of this study was to examine the effect of Brand l    ove, Self-exspressive, Brand trust, Brand commitment on Revisit intention in health services. This study is a quantitative study using purposive sampling method involving 130 outpatients who live in particular Tangerang and outside Tangerang, with visits about 2-3 times in the last year, and aged 18 years and over. Data analysis used Structural Equation Modeling (SEM). This research produces findings including self-expressive affects Brand love, Brand love affects Brand trust, and Brand commitment, Brand trust has no effect on Brand commitment, Brand trust affects revsit intention. There are several limitations to this study including only using a sample from one hospital, so the results may not be generalizable to other hospitals in Indonesia or other countries, an online questionnaire distribution system and the need to add other variables to expand the findings so that it is hoped that future researchers can fill these gaps.   Keywords: Brand love, self-expressive, brand trust, brand commitment, revisit intention, non-BPJS.